Who's Grocery Shopping Online and Why: Cross-Sectional Analysis of a Nationally-Representative Sample Since the Pandemic. (7th June 2021) - Lo, Amy; Duffy, Emily; Ng, Shu Wen
Abstract: Objectives: COVID-19 has created a new normal, affecting food purchasing behaviors, moving a portion of them online. It is unknown how these behavioral shifts may differ by sociodemographic characteristics and whether shifts may widen or diminish existing diet-related disparities. To fill these gaps, we use nationally-representative Consumer Panel survey data to examine shifts in online grocery shopping by sociodemographic characteristics. Methods: The Nielsen COVID-19 Shopper Behavior Survey was administered to a subset of Nielsen Homescan panel participants in March-April 2020 ( n  = 17, 262 households (HH)). We describe survey-weighted HH sociodemographic characteristics and reasons for online shopping. Survey weighted-multivariable logistic regression was used to examine sociodemographic correlates of reported increases in online food shopping. Results: One third (34%) of our survey-weighted sample said they shopped for groceries online more since COVID-19, and 60% of these HH reported planning to continue shopping online after COVID-19. In adjusted analyses, all age groups (40–54 y, 55–64y, 65 + y) had lower odds of online shopping than heads of HH 39 years or younger (all OR = 0.7, P  < 0.001). Lower educated (high school or less) HH had lower odds of online shopping compared to higher educated (college or more) HH (OR = 0.7, P  < 0.001). HH in the South had higher odds of online shopping than those in the Northeast (OR = 1.2, P  = 0.006). Compared to Non-Hispanic (NH) white HH, Hispanic HH had higher odds of online shopping (OR = 1.2, P  = 0.02), and NH Asian HH had lower odds of online shopping (OR = 0.8, P  = 0.02). HH with children had higher odds of online shopping compared to households without children (OR = 1.4, P  < 0.001). Of those who said they would increase the amount of online shopping they did for everyday items including food (37%), the top reasons were to avoid public germs and COVID-19 (81%), to take advantage of the convenience (44%) and to access a better selection (17%). Conclusions: There are disparities in shifts in online shopping behaviors due to COVID-19. Understanding these disparities can inform public health nutrition interventions related to online food shopping. We will assess the August 2020 survey as the pandemic may further change food shopping habits. Funding Sources: Arnold Ventures & National Institutes of Health